2016
DOI: 10.1007/s10815-016-0704-6
|View full text |Cite
|
Sign up to set email alerts
|

Follicular fluid soluble receptor for advanced glycation endproducts (sRAGE): a potential protective role in polycystic ovary syndrome

Abstract: Purpose To explore the relationships between the soluble receptor for advanced glycation endproducts (sRAGE) and the outcome parameters following in vitro fertilization-embryo transfer (IVF-ET) in patients with polycystic ovary syndrome (PCOS) and investigate the protective effect of sRAGE in PCOS development regarding inflammation. Methods We conducted a prospective analysis of a subsample of 74 participants from the Reproductive Medical Center of the First Affiliated Hospital of Zhengzhou University. We quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 34 publications
0
13
0
1
Order By: Relevance
“…A state of chronic hyperglycemia has been associated with increased formation of advanced glycation end produts (AGE) and their accumulation in tissues including those of the oral cavity [25]. It has been reported that increased interactions between AGE and their receptors are associated with an increased severity of tissue inflammation and raised levels of proinflammatory cytokines in saliva, follicular fluid, and serum [26][27][28]. As all of the patients with T2DM included in the present study had HbA1c levels higher than 8%, it is likely that there was an increased expression of AGE and interactions between AGE and receptor of AGE among individuals in group 2 (regardless of the presence or absence of peri-implantitis) compared to group 1.…”
Section: Discussionmentioning
confidence: 99%
“…A state of chronic hyperglycemia has been associated with increased formation of advanced glycation end produts (AGE) and their accumulation in tissues including those of the oral cavity [25]. It has been reported that increased interactions between AGE and their receptors are associated with an increased severity of tissue inflammation and raised levels of proinflammatory cytokines in saliva, follicular fluid, and serum [26][27][28]. As all of the patients with T2DM included in the present study had HbA1c levels higher than 8%, it is likely that there was an increased expression of AGE and interactions between AGE and receptor of AGE among individuals in group 2 (regardless of the presence or absence of peri-implantitis) compared to group 1.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we have found that follicular fluid sRAGE levels were negatively correlated with VEGF in PCOS [9] . EGF-like growth factors, amphiregulin (AREG), betacellulin (BTC), epiregulin (EREG) can bind and activate epidermal growth factor receptor (EGFR) [10,11] .…”
Section: Introductionmentioning
confidence: 73%
“…To date, emerging evidences have supported that PCOS was related to hyperandrogenism, insulin resistance and chronic inflammation [19] . Our previous study shown that sRAGE concentrations were decreased in the follicular fluid of PCOS patients, and these sRAGE were inversely associated with VEGF, TNF-α, IL-6, and CRP protein levels [9] . According to Boulanger, the activation of AGEs-RAGE axis in human peritoneal mesothelial cells can induce the release of VEGF and subsequently the formation of capillary tubes, while anti-receptor for AGEs (RAGE) antibody reduced capillary tube formation [20] .…”
Section: Age-rage Axis Can Activate P21 Ras Mapk (P38) Pi3k Nf-kb mentioning
confidence: 87%
“…One research supported our point that sRAGE could represent as a biomarker and a potential therapeutic target for ovarian dysfunction in PCOS [8] . Interestingly, we have found that follicular uid sRAGE levels were negatively correlated with VEGF in PCOS [9] . EGF-like growth factors, amphiregulin (AREG), betacellulin (BTC), epiregulin (EREG) can bind and activate epidermal growth factor receptor (EGFR) [10] .…”
Section: Introductionmentioning
confidence: 73%
“…To date, emerging evidences have supported that PCOS was related to hyperandrogenism, insulin resistance and chronic in ammation [19] . Our previous study shown that sRAGE concentrations were decreased in the follicular uid of PCOS patients, and these sRAGE were inversely associated with VEGF, TNF-α, IL-6, and CRP protein levels [9] . According to Boulanger, the activation of AGEs-RAGE axis in human peritoneal mesothelial cells can induce the release of VEGF and subsequently the formation of capillary tubes, while anti-receptor for AGEs (RAGE) antibody reduced capillary tube formation [20] .…”
Section: Age-rage Axis Can Activate P21 Ras Mapk (P38) Pi3k Nf-kb mentioning
confidence: 87%